2011
DOI: 10.1111/j.1538-7836.2010.04104.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden as a risk factor for preterm birth – a population‐based nested case–control study

Abstract: To cite this article: Hiltunen LM, Laivuori H, Rautanen A, Kaaja R, Kere J, Krusius T, Rasi V, Paunio M. Factor V Leiden as a risk factor for preterm birth -a population-based nested case-control study. J Thromb Haemost 2011; 9: 71-8.Summary. Background: Preterm birth is a major cause of neonatal morbidity and mortality, occurring in 5-13% of deliveries in developed countries. Genetic thrombophilia can theoretically contribute to the induction of preterm delivery, but the role of thrombophilia as risk factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…A study of 100 000 consecutive pregnancies in Finland showed F5 G1691A, but not F2 polymorphism, to triple the risk for late preterm birth at or after 32 weeks of gestation (Hiltunen et al , ), A population‐based study of women delivering a singleton live birth found PE, fetal distress, SGA or PA in over half of all medically indicated preterm deliveries (less than 35 weeks; Ananth & Vintzileos, ). A nested case‐cohort study of pregnant women from the Danish National Birth Cohort showed that F5 G1691A increased the risk of severe PE (mean OR 1·6), severe FGR/SGA (defined bellow the 3rd percentile; mean OR 1·4) and clinically symptomatic PA (mean OR 1·7; Lykke et al , ).…”
Section: Thrombophilia and Placenta‐mediated Pregnancy Complicationsmentioning
confidence: 99%
“…A study of 100 000 consecutive pregnancies in Finland showed F5 G1691A, but not F2 polymorphism, to triple the risk for late preterm birth at or after 32 weeks of gestation (Hiltunen et al , ), A population‐based study of women delivering a singleton live birth found PE, fetal distress, SGA or PA in over half of all medically indicated preterm deliveries (less than 35 weeks; Ananth & Vintzileos, ). A nested case‐cohort study of pregnant women from the Danish National Birth Cohort showed that F5 G1691A increased the risk of severe PE (mean OR 1·6), severe FGR/SGA (defined bellow the 3rd percentile; mean OR 1·4) and clinically symptomatic PA (mean OR 1·7; Lykke et al , ).…”
Section: Thrombophilia and Placenta‐mediated Pregnancy Complicationsmentioning
confidence: 99%
“…Researchers have identified a few potential maternal risk factors associated with preterm birth including maternal hypertension [5], Factor V Leiden [19], lower genital tract inflammatory milieu [20], prior preeclampsia [18], and Crohn’s disease [21]. Not only were these trials limited in statistical power, few studies explored potential risk factors for ePTB, which has a higher risk for poor health outcomes [13, 22].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Hiltunen et al. [29] in a Finish case–control study found FV Leiden to be associated with late preterm delivery (gestational age [GA] 32–36 weeks), but not with very preterm delivery (GA < 32 weeks); PTM was not associated with preterm delivery. We did not find evidence of any association with very preterm delivery.…”
Section: Discussionmentioning
confidence: 94%